Ser, esencia y atributos divinos: el conocimiento de Dios en la metafísica tomasiana según la interpretación de Jean-Luc Marion - Ocampo, Fernanda (2019)
“Being, Essence and Divine Attributes: The Knowledge of God in Thomasian Metaphysics according to the Interpretation of Jean-Luc Marion”. For Jean-Luc Marion, the thought of Aquinas is not to be understood under the parameters of the onto-theo-logical metaphysics defined by Martin Heidegger. This implies with respect to God that, if he is no longer to be called “supreme being” (ens) since for Aquinas God is revealed as the “Act of Being” (esse lacking in essence), then he is characterized by his absolute unknowability. To support this interpretation, Marion turns to a series of theses that he considers are derived from the reading of some of Aquinas’ texts. In this article, some of these theses are analyzed in relation to those texts (and to some new ones), and an alternative reading to the one of the author is proposed. It is particularly stressed that, in the eyes of Thomas Aquinas, it is possible to attribute the notion of “essence” to God, and to reach a true but imperfect and limited knowledge of the divine reality based on the positive predication of certain absolute perfections that are found in creatures.